PENGARUH PEMBERDAYAAN KARYAWAN TERHADAP MOTIVASI BERPRESTASI DAN KINERJA KONTEKSTUAL PADA KARYAWAN PT. BANK SYARIAH MANDIRI BANDA ACEH - Febriana Fardilla, Murkhana (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
This study aims to determine the effect of employee empowerment on achievement motivation and the contextual performance of employees. The emprical study conducted at employee PT. Bank Syariah Mandiri used a questionaire as a research instrument, which samples in this study of 100 respondent. Probability Sampling is used as a sampling technique with census. Methods simple linear regression is used a method of data analysis using software IBM SPSS 20. These result indicate that the employee empowerment positive and significant impact on achievement motivation, employee empowerment have a postitive and significant effect on contextual performance.Keywords : Employee empowerment, achievemernt motivation, contextual performance